WOMEN’S EMANCIPATION IN MOVIE: A FEMINISM ANALYSIS IN BIRDS OF PREY BY CATHY YAN - Anitiya Indah Fitrotun Ni'mah (Universitas Muria Kudus, 2022)
Abstract: This study aims to determine the results analysis of the emancipation of Harley Quinn in the Birds Of Prey movie (And the Fantabulous Emancipation of one Harley Quinn) based on feminism theory. The data analysis, the writer used descriptive analysis techniques. The method used is a descriptive qualitative methods, the writer used data in the form of movie scenes because the data comes from pictures of scenes, dialogue and text. The writer analyzing them by watching and reading the transcripts of the movies, and then describe and present them. The results of this study showed emancipation of Harley Quinn is her struggle to survive and fight against the enemies, even though everyone underestimated because she has been regardless the influence of the Joker who previously always protected her. However in the end she was able to prove her independence to rise from adversity and start a new purpose in life. So she and her friends formed Birds of Prey to quell evil.